Liberals and conservatives can show similarities in negativity bias. Issue 3 (27th June 2014) - Brandt, Mark J.; Wetherell, Geoffrey; Reyna, Christine
Abstract Negativity bias may underlie the development of political ideologies, but liberals and conservatives are likely to respond to threats similarly. We review evidence from research on intolerance, motivated reasoning, and basic psychological threats that suggest liberals and conservatives are more similar than different when confronting threatening groups, situations, and information.